DEP-on-a-Chip: Dielectrophoresis Applied to Microfluidic Platforms - Zhang, Haoqing; Chang, Honglong; Neuzil, Pavel (Micromachines, 2019)
Dielectric particles in a non-uniform electric field are subject to a force caused by a phenomenon called dielectrophoresis (DEP). DEP is a commonly used technique in microfluidics for particle or cell separation. In comparison with other separation methods, DEP has the unique advantage of being label-free, fast, and accurate. It has been widely applied in microfluidics for bio-molecular diagnostics and medical and polymer research. This review introduces the basic theory of DEP, its advantages compared with other separation methods, and its applications in recent years, in particular, focusing on the different electrode types integrated into microfluidic chips, fabrication techniques, and operation principles.
Keywords: two-dimensional electrodes; dielectrophoresis; three-dimensional electrodes; parallel electrodes; microfluidics; castellated electrodes; interdigitated electrode